Multicultural Indonesia Reflected in Hendri Teja’s Tan Novel - Sri Utami Budi; Henny Indarwaty (Alphabet: A Biannual Academic Journal on Language, Literary, and Cultural Studies, 2018)
Reading a literary work might give us an idea of the situations of society in a particular time. In the sociology of literature, this phenomenon is referred as a mirror of an age. This means that a literary work does not simply describe the conditions of a society, but also values the tradition of a society. Taking Tan novel as its object, this study to see the description of Indonesia’s condition, at the time when the novel was composed by Hendri Teja. Alan Swingewood and Diana Laurenson’s idea which sees literary work is the reflection of the age are used as an approach to this study. The data which were taken from the novel were analized by relating them to the secondary data taken from articles discussing the situation of society depicted in the novel. The study concluded that the description in Tan novel does not only resemble Indonesian conditions but it also portrays values in the society, i.e. plurality in religion and social class and general agreement in decision making. The way the society value multiculturalism reflects the greatness of Indonesian people to accept the difference and their practicing of democratic system. In addition, this study also found out that this novel also criticize long running problem between the working class and the capital owner in Indonesian society.